ALIH AKSARA DAN ALIH BAHASA TEKS RISALAH MAU’IZAH HASANAH DISUSUN OLEH IMAM MAULANA ABDUL MANAF KHATIB AMIN BATANG KABUNG KOTO TANGAH TABING PADANG - Syofiani, Lidya; Nurizzati, Nurizzati; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2018)
This article aims to present: (1) the revised text of the Treatise Mau'izah Hasanah compiled by Imam Maulana Abdul Manaf Khatib Amin Stem kabung Koto Tangah, Padang Tabing (2) Interpreting the text of the Treatise Mau'izah Hasanah compiled by Imam Maulana Abdul Manaf Khatib Amin Stem kabung Koto Tangah Tabing field. This type of research is qualitative research with a focus to the field of Philology, namely research and critique text edition that aims to produce an edition of the text that can be justified scientifically based on the stages and methods philological research. . The object of this research is the text Mau'izah Hasanah Treatise compiled by Imam Maulana Abdul Manaf Khatib Amin Stem kabung Koto Tangah Tabing field. The methods used in this research tailored to the stage of research. In this research, there are four stages of research are used. The results of this study is to present a text that can be read and understood by the community now about the text of the Treatise Mau'izah Hasanah compiled by Imam Maulana Abdul Manaf Khatib Amin Stem kabung Koto Tangah Tabing field.Keywords: philology, transliteration, translation